Accounting Earning Response Coefficient: Synthesis of Earning Responses - Ratna Wijayanti Daniar Paramita (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
The research objective was to compare the value of the Earnings Response Coefficient (ERC) with the Accounting Earnings Response Coefficient (AERC). Research on earnings response has been carried out with mixed results using the Earnings Response coefficient. Several researchers provide arguments and highlight the weaknesses of the ERC measure used to measure earnings quality. This study suspects that the size of the ERC may be different if cash flows are applied and not only earnings based on historical cost or accrual principles. The synthesis process is carried out to generate new concepts and then comparisons will be made of the ERC and AERC results. The study was conducted on 69 companies listed on the Indonesia Stock Exchange in 2014-2017. The results of the different test results for the ERC and AERC values on the Paired Sample Test value are significant (0.000), which means that the value obtained by adding CFO to the AERC equation is different from the ERC concept. These results indicate that the earnings quality resulting from the AERC regression by adding the CFO value to the AERC equation is the earnings quality after being corrected by CFO, so that the AERC value reflects the real earnings quality.